Serotonin syndrome caused by a CYP2C19-mediated interaction between low-dose escitalopram and clopidogrel: a case report - Wu, Jianhong; Yu, Jiao; Qu, Kankan; Yin, Jiajun; Zhu, Chunming; Liu, Xiaowei (Frontiers in Psychiatry, 2023)
Background: Serotonin syndrome has been recognized as a serious adverse reaction of antidepressants, and characterized by sudden or severe autonomic nerve dysfunction and neuromuscular symptoms. Without accurate diagnosis and prompt treatment, serotonin syndrome progresses rapidly and may be life-threatening. It is usually related to the dose of 5-hydroxytryptamine drugs and the dose is the basis of diagnosis. Therefore, serotonin syndrome induced by low-dose antidepressants rarely occurs, and clinicians are more likely to misdiagnose patients with similar symptom who take low-dose of antidepressants. Here we present a case study of serotonin syndrome caused by quite a low-dose of escitalopram, which is not common in past references. Case summary: The patient was a 74-year-old Asian woman with a 42-year history of schizophrenia. After six weeks of antidepressant treatment, our patient presented with characteristic myoclonus in the lower limbs and eyes closed with flutter. Initially, she was misdiagnosed with neuroleptic malignant syndrome (NMS) due to the medication of antipsychotics, and received corresponding treatment including discontinuation of clozapine. However, her symptoms persist and then therapeutic drug monitoring was introduced after clinical pharmacist’s participation. Finally, she was diagnosed with serotonin syndrome due to concentration of escitalopram reached the warning level. After that, the patient received treatment modification and her clinical outcome was satisfactory without any other seriously adverse reaction. Gene detection was also performed and a cytochrome P450 enzyme (CYP) 2C19-mediated interaction between low-dose escitalopram and clopidogrel seems to be a possible mechanism. Conclusion: Data on this is extremely scarce and to the best of our knowledge, serotonin syndrome caused by low-dose of antidepressants has yet not to any great extent been discussed in the literature. Our case provide more clinical experience in the treatment of serotonin syndrome.